2014
DOI: 10.1676/13-087.1
|View full text |Cite
|
Sign up to set email alerts
|

Range expansion and the breakdown of Bergmann's Rule in Red-Bellied Woodpeckers (Melanerpes carolinus)

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 28 publications
(25 reference statements)
0
16
0
Order By: Relevance
“…Red‐bellied Woodpecker pre‐ and post‐expansion occurrences, models, and niche overlap values. Occurrence data (red dots) obtained from Audubon Christmas Bird Count and museum specimen locality information via Kirchman and Schneider (); CBC locations where Red‐bellied Woodpeckers were not reported are shown by gray dots. Warmer colors indicate a higher probability of species occurrence.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Red‐bellied Woodpecker pre‐ and post‐expansion occurrences, models, and niche overlap values. Occurrence data (red dots) obtained from Audubon Christmas Bird Count and museum specimen locality information via Kirchman and Schneider (); CBC locations where Red‐bellied Woodpeckers were not reported are shown by gray dots. Warmer colors indicate a higher probability of species occurrence.…”
Section: Resultsmentioning
confidence: 99%
“…As a generalist, the Red‐bellied Woodpecker has the potential to adapt to rapidly changing environments. Kirchman and Schneider () found that the northernmost individuals are larger post‐expansion, perhaps indicating that a shift in body size has enabled expansion into colder regions. This supports the idea that generalist species can expand their environmental breadth and range due to adaptation or plasticity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations